The marketing-sales organizations as the way of internationalizing of the small and medium enterprises - Piorunowska-Kokoszko Joanna (Management)
The internationalization is becoming a part of company’s strategy, requiring some effort for getting its success. The present article is aimed at showing that joining the sale group is one of many ways of internationalizing activity for small and medium enterprises. The article presents the roles of sales group activity, its typical structure and opportunities and threats for its functioning. Based on collected data it was pointed, that companies, especially SME should analyze perspective for joining the sale group in their supply chain or seek for other forms of cooperation supporting their foreign market entry. Cooperation allows in relatively short time to achieve first results. Resignation of cooperation should be a conscious decision of management. Such decision, as every one, can bring expected benefits or be difficult to reconstruct it in the future.